Detection of Peripheral Arterial Disease Using Ankle Brachial Index and Its Correlation with Glycated Haemoglobin, Low-Density Lipoprotein, High- Density Lipoprotein and Triglycerides Level in Patients with Type-2 Diabetes - Dr Sarika Singla; Dr Pankaj Gandhi; Dr Prakash Shenoy (International Journal of Pharma and Bio Sciences, 2024)
Peripheral arterial disease (PAD) is a prevalent complication of type-2 diabetes mellitus (T2DM) and is associated with significant morbidity and mortality. This study aimed to investigate the prevalence of PAD using ankle-brachial index (ABI) and its association with HbA1c, LDLc, HDLc, and triglycerides among T2DM patients. This prospective, observational study included 160 T2DM patients. ABI measurements were performed using a Doppler ultrasound device. Fasting blood samples were collected to measure HbA1c, LDLc, HDLc, and triglycerides levels. Data were analyzed using descriptive statistics, correlation analyses, and univariate and multivariate logistic regression models. The prevalence of PAD, defined as an ABI ≤ 0.9, was 45.6% (72 patients). PAD patients had significantly higher HbA1c levels (7.9 ± 1.2% vs. 7.2 ± 0.8%, p < 0.001), higher LDLc (121.8 ± 15.4 mg/dL vs. 108.6 ± 12.2 mg/dL, p < 0.001), and lower HDLc levels (45.6 ± 5.2 mg/dL vs. 51.3 ± 4.8 mg/dL, p < 0.001) compared to non-PAD patients. Triglyceride levels were also significantly higher in the PAD group (169.5 ± 22.1 mg/dL vs. 135.7 ± 18.3 mg/dL, p < 0.001). In univariate analysis, HbA1c, LDLc, and HDLc were significantly associated with PAD. In multivariate analysis, HbA1c (OR = 1.63, 95% CI: 1.12-2.38) and LDLc (OR = 1.02, 95% CI: 1.01-1.03) remained significant independent predictors of PAD. This study revealed a high prevalence of PAD among T2DM patients. HbA1c and LDLc were significant independent predictors of PAD. These findings highlight the importance of regular screening for PAD and optimizing glycemic control and lipid profiles to reduce the risk of this complication in T2DM patients.